2007
DOI: 10.1111/j.1600-065x.2007.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell receptor signaling to integrins

Abstract: Integrin adhesion receptors are critical for antigen recognition by T cells and for regulated recirculation and trafficking into and through various tissues in the body. T-cell receptor (TCR) signaling induces rapid increases in integrin function that facilitate T-cell activation by promoting stable contact with antigen-presenting cells and extracellular proteins in the environment. In this review, we outline the molecular mechanisms by which the TCR signals to integrins and present a model that highlights fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
109
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 163 publications
(281 reference statements)
1
109
0
2
Order By: Relevance
“…Previous work showed that tetraspanins stabilize integrins in their active conformations [13] and that CD9 promotes β1 activation [14]. Activation of LFA-1 integrin is regulated by the actin linker protein talin [15], which has been implicated in integrin "inside-out" signaling [16]. However, talin relocalization to the IS in CD9-and CD151-silenced T cells remained similar to control cells (Supporting Information Fig.…”
mentioning
confidence: 81%
“…Previous work showed that tetraspanins stabilize integrins in their active conformations [13] and that CD9 promotes β1 activation [14]. Activation of LFA-1 integrin is regulated by the actin linker protein talin [15], which has been implicated in integrin "inside-out" signaling [16]. However, talin relocalization to the IS in CD9-and CD151-silenced T cells remained similar to control cells (Supporting Information Fig.…”
mentioning
confidence: 81%
“…This implies that under physiologic settings, lymphocytes may employ ILPs as discrete subcellular '3D-reaction volumes' with 'signalosome'-like properties that amplify and sustain signaling by concentrating important molecules/activities 32,33 . Additionally, the presence of significant biomechanical inputs (i.e., cell-cell force application) at sights if ILP protrusion against the APC can be inferred from the imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The increased Ca 2+ levels then activate the protein phosphatase calcineurin (Klee et al, 1979) by disrupting the inhibitory effects of calmodulin. Calcineurin activation leads to the dephosphorylation of NFAT, allowing it to enter the nucleus, where it co-operates with other transcription factors to bind promoters (Burbach et al, 2007).…”
Section: Discussionmentioning
confidence: 99%